2021
DOI: 10.1155/2021/5596727
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019-Related Multisystem Inflammatory Syndrome in Children: A Systematic Review and Meta-Analysis

Abstract: Background. This study aimed to describe the clinical symptoms, laboratory findings, treatment, and outcomes of coronavirus disease 2019-related multisystem inflammatory syndrome in children to provide a reference for clinical practice. Methods. We employed a literature search of databases such as PubMed, Web of Science, EMBASE, and Johns Hopkins University for articles on COVID-19-related multisystem inflammatory syndrome in children published between April 1, 2020, and January 15, 2021. High-quality articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 75 publications
1
16
1
2
Order By: Relevance
“…Although children have been considered to develop mild symptoms compared to adults, recent studies have reported that COVID-19-related multisystem inflammatory syndrome can cause morbidity and mortality [ 34 , 35 ]. The recent rapid increase of cases among children could lead to an increase of severe cases in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Although children have been considered to develop mild symptoms compared to adults, recent studies have reported that COVID-19-related multisystem inflammatory syndrome can cause morbidity and mortality [ 34 , 35 ]. The recent rapid increase of cases among children could lead to an increase of severe cases in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Although conjunctivitis itself is largely benign and self-limiting, it can occur in up to 55% of children with COviD-19-related polyarthritis, a more serious condition requiring urgent attention. Therefore, children with conjunctival symptoms should be investigated for other associated symptoms, including rash, lymphadenopathy, and limb edema [17]. Swelling of the eyelids was found in 0.9% of COviD-19 patients, their irritation in 4.9% of individuals, most often in combination with conjunctival congestion [11,[18][19][20].…”
Section: Tablementioning
confidence: 99%
“…The pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and its related disease (COVID-19) represents a major challenge for humans. To date, COVID-19 has caused more than 3 million deaths, leading to economic troubles in several countries [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has a multisystem involvement affecting not only the lungs but also the cardiovascular, nervous, and gastrointestinal systems. In adults, and especially in children, COVID-19 has led to a multisystem inflammatory syndrome [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%